Predictors of Loss of Asthma Control Induced by Corticosteroid Withdrawal - Jose Belda; Krishnan Parameswaran; Catherine Lemière; Dennis Kamada; Paul M O'Byrne; Frederick E Hargreave (Canadian Respiratory Journal)
BACKGROUND: Asthma guidelines recommend reducing the dose of inhaled corticosteroids after establishing control.